Efficacy of negative pressure wound therapy using suction drain in the management of chronic wounds - Imran, Mohammed Kashif; K., Mohan Kumar; P. N., Sreeramulu; ., Bhaskaran; K., Krishna Prasad; C. A., Shashirekha; Dave, Prakash (International Surgery Journal, 2018)
Background: Chronic non-healing wounds are one of the major burden to the patients in the present era and covers about 1% of adult population and 3.6% of the population greater than 65 years. Chronic leg wounds are the common cause of morbidity and its prevalence in the community range from 1.9 to 13.1%. Indian studies show the prevalence of chronic wounds of around 4.5/1000 population. Recent studies have shown that application of a sub atmospheric pressure in a controlled manner to the wound site helps significantly in wound healing. Aim of the present study is to assess the efficacy of topical negative pressure moist wound dressings in wound healing process in chronic wounds and to prove that negative pressure dressings can be used as a much better treatment option than conventional saline dressings in the management of chronic wounds. Methods: After 10 days, in study group the mean rate of granulation tissue formation, mean graft, mean hospital stay was 81.7%,80.6%, 34.7 days respectively and the same in control group it is 41.9%. ,60.45%, 58.60 days respectively. Results: To conclude, topical negative pressure dressing’s help in faster healing of chronic wounds and better graft take up and reduces hospital stay of these patients. Conclusions: The database of our retrospective study regarding age and sex incidence, clinicopathological features and therapeutic outcome was comparable to other studies in various literatures.